Em busca de um novo começo: uma reflexão sobre a transferência e a contratransferência no atendimento de uma paciente borderline - Bedoya, Natalie de Jesus Santana (2009)
In post-modernity, the psychoanalytical practice has been facing the challenge of dealing with changes in subjectivity and new psychopathological disorders. In this scenario, it comes the Borderline patient, bringing up challenges and opportunities in psychoanalysis that are gaining more relevance in the clinical and scientific discussions of the country, requiring analysts dedication to reflect on how to handle this sort of patiens within the clinical practice. Given this reality and in search for a more clinically effective approach, the objective of this survey was to deepen the current insights on the Borderline Personality disorder, with the intention of undertanding specific aspects of transference and countertransference demand that are experienced in the psychoanalysis process. This work was accomplished through a qualitative approach based on the clinical method of psychoanalysis, following the theoretical framework of Donald Winnicott. Having reflected on how to manage a borderline case, this survey outlines specific issues concerning transference and countertransference. It was observed that the problem lies at the confluence of the existential suffering of the patient and the countertransferencial suffering of the analyst, that requires professional sensitivity so as to ensure an appropriate approach aligned with the patient needs, indeed considering its own limits. In sum, the analysis process should be oriented to provide the patient a more integrated self